1964
DOI: 10.1152/jappl.1964.19.6.1234
|View full text |Cite
|
Sign up to set email alerts
|

Effect of embalming on the mechanical properties of beef bone

Abstract: Small tension and compression specimens were made from beef femurs and alternate specimens were embalmed. The stress-strain diagrams were then obtained using automatic recording equipment. From this diagram the modulus of elasticity, ultimate strength, and maximum strain to failure were determined. The hardness of all specimens was measured. A statistical evaluation of the data indicated that embalming causes a significant reduction (12%) in the ultimate compressive strength of beef bone, but only very slight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
3

Year Published

1970
1970
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(41 citation statements)
references
References 0 publications
1
37
0
3
Order By: Relevance
“…Several studies have already evaluated the effect of different storage methods on the mechanical properties of bone (McElhaney et al 1964, Pelker et al 1984, Roe et al 1988, Goh et al 1989, Linde and Sorensen 1993, Kang and Kim 1995, Currey et al 1995, Wilke et al 1996, but the maximum storage time in these studies was 3 months. Cadaver bodies are generally stored for 1 year or more after they are embalmed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have already evaluated the effect of different storage methods on the mechanical properties of bone (McElhaney et al 1964, Pelker et al 1984, Roe et al 1988, Goh et al 1989, Linde and Sorensen 1993, Kang and Kim 1995, Currey et al 1995, Wilke et al 1996, but the maximum storage time in these studies was 3 months. Cadaver bodies are generally stored for 1 year or more after they are embalmed.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have already been performed to investigate the effects of embalming or freezing on the mechanical properties of bones (McElhaney et al 1964, Sedlin 1965, Pelker et al 1984, Panjabi et al 1985, Roe et al 1988, Goh et al 1989, Linde and Sorensen 1993, Currey et al 1995, Kang and Kim 1995, Hamer et al 1996. However, in these studies the maximum storage time was 3 months, whereas cadaver specimens are generally stored for much longer periods.…”
mentioning
confidence: 99%
“…McElhaney [7] found that embalmed human femur has an ultimate strength of 140 MPa at quasi-static rate, while the strength at high rate (1500/s) was 300 MPa in the longitudinal direction of the bone. In general, direct comparisons between embalmed and fresh bone are not recommended because of the significant effects of embalming on bone microstructure and its constituents, leading to altered bone mechanical properties [8]. In an attempt to quantify these effects, McElhaney et al [8] conducted a comparative study and found that embalming caused a 12 % reduction in ultimate compressive strength.…”
Section: Comparison Of Cortical Bone Studiesmentioning
confidence: 99%
“…In general, direct comparisons between embalmed and fresh bone are not recommended because of the significant effects of embalming on bone microstructure and its constituents, leading to altered bone mechanical properties [8]. In an attempt to quantify these effects, McElhaney et al [8] conducted a comparative study and found that embalming caused a 12 % reduction in ultimate compressive strength. After the 12 % reduction in strength due to embalming was corrected, the range of ultimate strength found for human bone by McElhaney [7] would be 168-355 MPa, similar to the values found in this study.…”
Section: Comparison Of Cortical Bone Studiesmentioning
confidence: 99%
See 1 more Smart Citation